Faecal incontinence—a comprehensive review - Dexter, Eloise; Walshaw, Josephine; Wynn, Hannah; Dimashki, Safaa; Leo, Alex; Lindsey, Ian; Yiasemidou, Marina (Frontiers in Surgery, 2024)
Faecal incontinence (FI) is a distressing and often stigmatising condition characterised as the recurrent involuntary passage of liquid or solid faeces. The reported prevalence of FI exhibits considerable variation, ranging from 7 to 15% in the general population, with higher rates reported among older adults and women. This review explores the pathophysiology mechanisms, the diagnostic modalities and the efficiency of treatment options up to date.A review of the literature was conducted to identify the pathophysiological pathways, investigation and treatment modalities.This review provides an in-depth exploration of the intricate physiological processes that maintain continence in humans. It then guides the reader through a detailed examination of diagnostic procedures and a thorough analysis of the available treatment choices, including their associated success rates. This review is an ideal resource for individuals with a general medical background and colorectal surgeons who lack specialized knowledge in pelvic floor disorders, as it offers a comprehensive understanding of the mechanisms, diagnosis, and treatment of faecal incontinence (FI).